STRATEGI PENGURANGAN BIAYA UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF PERUSAHAAN - Mezsas Purba, Yudha Sadry; Harefa, Cakra Famati; Manalu, Dauster; Saribu, Ardin Dolok; Ambarita, Neibi Ezenia; Siagian, Marianto Yus; Simanjuntak, Sherlyna; Yana Br Ginting, Audira Hendri (Komunitas Manajemen Kompetitif, 2025)
The main objective of this paper is to analyze the relevance of cost reduction strategies as a cost management approach in improving the competitive advantage of companies. Cost reduction strategies, such as target costing, activity-based costing, and kaizen costing. This study focuses on the target costing approach. Target costing is a cost management method that starts from determining the selling price based on market needs, then setting a target cost to achieve the desired level of profit. With this approach, companies can design efficient products from the early stages, without sacrificing quality and still meeting consumer expectations. The study was conducted through literature studies and reviews of major journals and various other supporting sources. The results of the analysis show that target costing is not only effective in reducing production costs, but also encourages innovation, collaboration between divisions, and strong market orientation. This strategy is very relevant to be applied to industries facing high cost pressures and tight competition. Thus, target costing has proven to be a strategic tool in creating efficiency as well as sustainable competitive advantage. Keywords: Target costing, Cost reduction, Competitive advantage, Efficiency, Cost strategy